Расложите выражение на множители по формуле а^2 - b^2 = (a - b) (a+b) 1) 16x^2 - 1 2) a^2 - 25b^2 3) x^4y^4 - 1 4) 25t^2 - (2z+3t)^2

2004by2013 2004by2013    3   27.08.2019 16:30    0

Ответы
AндрeйTh AндрeйTh  05.10.2020 23:03
Вот все решение надеюсь
Расложите выражение на множители по формуле а^2 - b^2 = (a - b) (a+b) 1) 16x^2 - 1 2) a^2 - 25b^2 3)
ПОКАЗАТЬ ОТВЕТЫ
Bublick08 Bublick08  05.10.2020 23:03
1). 16x^2-1=(4x)^2-1^2=(4x-1)(4x+1); 2). a^2-25b^2=(a)^2-(5b)^2=(a-5b)(a+5b); 3). x^4y^4-1=(x^2y^2)^2-1^2=(x^2y^2-1)(x^2y^2+1); 4). 25t^2-(2z+3t)^2=(5t)^2-(2z+3t)^2=(5t-(2z+3t))(5t+(2z+3t)).
ПОКАЗАТЬ ОТВЕТЫ
Другие вопросы по теме Алгебра